THE EFFECT OF ABDURAHMAN ASSUDAIS VIDEOS TOWARDS STUDENTS MOTIVATION IN LEARNING SPEAKING SKILL AT GLOBAL ENGLISH COMMUNITY MEMBERS - Baiq Liany Puspita Dewi (Sinar Lima, 2024)
The researcher interested to analyze the effect of teaching technique which is made by Abdurahman Assudais in the form of videos towards students’ motivation in learning English especially for speaking skill. The researcher designs used in this research was experimental design quasi experimental. In quasi experiments, the researceher used control and experimental group but did not randomly assign participant to groups. They intact groups available to the researcher. In this research used the form non-equivalent (pre-questionnaire test and post-questionnaire test) control group design in which this form was popular approach to quasi experiments, the experimental group A and the control group B were selected without random assignment. In technique of data analysis, the researcher applyed the statistical analysis and inferential statistics. The data of students’ score has been taken from the beginning test till the end of the test. The first question was given to the experimental class which received treatment using a videos by Abdurahman Assudais. The researcher used a questionnaire. The number of samples is 10 students. The results of the questionnaire presented showed that students who received treatment had an increase in motivation scores, this indicated that there were no students who had low motivation. Furthermore, the total average score of the experimental class is 805. According to the Five Point Likert scale, the average score indicates that students have a high level of motivation. Researchers used questionnaire. The number of samples is 10 students. The results of the questionnaire presented showed that students who were not treated experienced an increase in motivation scores, this indicated that there were no students who had low motivation. Furthermore, the total average score of the experimental class was 852. Based on the Five Point Likert scale, the average score indicated that students had a high level of motivation. Therefore, members of the Global English Community at Undikma Mataram, especially in the control class, have high motivation in learning speaking skills even without the videos treatment by Abdurahman Assudais.Based on research findings and data analysis in the previous chapter, it can be concluded that gec members, in this case the experimental class, have a high level of motivation in learning speaking skills. The data shows that 10 experimental class students who have low motivation in learning speaking skills have improved after being given treatment using videos from Abdurahman Assudais. Data calculations also show that the control class''s motivation also increases without any learning video treatment. The results illustrate that the total motivation score of the control class was higher than the experimental class where the score difference between the two was 117. Therefore, the learning motivation of the two classes increased and the video from Abdurahman Assudais had an effect on increasing the motivation to learning speaking skills of Global English Community members.